Rules and regulations of The United Brothers' Birmingham Benefit Society (London : J.S. Forsaith & Son, Printers (T.U.), 1908)
1908 1908 1900s 18 pages 4 admitted by paying his contribution and threepence for a book of rules and card, but if such person be not approved, his deposit money will be returned: but if such person should not attend the second meeting night after proposition, his deposit money will be forfeited to the funds of this society. Members joining this society between January and April will be allowed twelve months share by paying up the back arrears, and those joining between July and September to be allowed six months share by paying up all arrears due from July, but no member to be entitled to any benefits until six calendar months after his election. Any member not producing his card on pay night, shall pay one penny for a new one. Members removing their residence shall give notice to the secretary the following meeting night, or be fined sixpence. 3. That each person before he becomes a member of this society shall declare that he is not under 18, or above 35 years of age, and that he is free from all infirmity both bodily and mentally; he shall not follow any trade or calling that the society may consider dangerous to health, such as plumbing, painting, water gilding, or any other pernicious trade; he shall give such reference to character as the society may require, together with his occupation; and after he becomes a member of this society, should it at any time be found that he is such a person as this rule deems ineligible, or that he has made any false statements to gain admission, he shall be excluded and forfeit all claim to the stock and burial funds of this society. N.B. — Any member proposing a person to become a member of this society knowing him to be troubled with any periodical complaint, shall on proof thereof be excluded. 4. That this society appoint a fit and proper person who is not a member to be their secretary, who shall receive fourpence per quarter from each member for his services; he shall attend the society on their meeting 345/7/2/2